GABAB Receptor-Mediated Impairment of Intermediate Progenitor Maturation During Postnatal Hippocampal Neurogenesis of Newborn Rats - Gustorff, Charlotte; Scheuer, Till; Schmitz, Thomas; Bührer, Christoph; Endesfelder, Stefanie (Frontiers in Cellular Neuroscience, 2021)
The neurotransmitter GABA and its receptors assume essential functions during fetal and postnatal brain development. The last trimester of human pregnancy and early postnatal life involve a vulnerable period of brain development. In the second half of gestation, there is a developmental shift from depolarizing to hyperpolarizing in the GABAergic system, which might be disturbed by preterm birth. Alterations of the postnatal GABA shift is associated with several neurodevelopmental disorders. In this in vivo study, we investigated neurogenesis in the dentate gyrus in response to daily administration of pharmacological GABAA (DMCM) and GABAB (CGP 35348) receptor inhibitors to newborn rats. Six-day-old Wistar rats (P6) were daily injected (i.p.) to postnatal day 11 (P11) with DMCM, CGP 35348 or vehicle to determine the effects of both antagonists on postnatal neurogenesis. Due to GABAB receptor blockade by CGP 35348, immunohistochemistry revealed a decrease in the number of NeuroD1 positive intermediate progenitor cells and a reduction of proliferative Nestin-positive neuronal stem cells at the dentate gyrus. The impairment of hippocampal neurogenesis at this stage of differentiation is in line with a significantly decreased RNA expression of the transcription factors Pax6, Ascl1 and NeuroD1. Interestingly, the number of NeuN-positive postmitotic neurons was not affected by GABAB receptor blockade, although strictly associated transcription factors for postmitotic neurons, Tbr1, Prox1 and NeuroD2, displayed reduced expression levels, suggesting impairment by GABAB receptor antagonization at this stage of neurogenesis. Antagonization of GABAB receptors decreased the expression of neurotrophins (BDNF, NT-3 and NGF). In contrast to the GABAB receptor blockade, the GABAA receptor antagonization revealed no significant changes in cell counts, but an increased transcriptional expression of Tbr1 and Tbr2. We conclude that GABAergic signalling via the metabotropic GABAB receptor is crucial for hippocampal neurogenesis at the time of rapid brain growth and of the postnatal GABA shift. Differentiation and proliferation of intermediate progenitor cells are dependent on GABA. These insights become more pertinent in preterm infants whose developing brains are prematurely exposed to the postnatal stress and predisposed to poor neurodevelopmental disorders, possibly as sequelae of early disruption in GABAergic signaling.